Penyelesaian Kredit Macet Terkait Adanya Tagihan Utang Pajak Debitur di Bank BRI Kantor Cabang Medan Thamrin - Arfandi, Muhammad; Ginting, Budiman; Barus, Utary Maharany; Siahaan, Rudy Haposan (Journal of Law & Policy Review, 2024)
The implementation of mortgage execution, execution (parate execution) must be based on a promise to sell under one's own power as regulated in Article 1178 paragraph (2) of the Civil Code, so that it is an implementation of an agreement and accompanied by a mortgage deed grosse which is intended "For the sake of Justice Based on the Almighty Godhead" This research is descriptive analytical in nature. The type of research used in this thesis is empirical legal research. Types and sources of data that will be used secondary and primary data. Data analysis was carried out to answer the problems studied using qualitative methods. Research using qualitative methods starts from assumptions about reality or social phenomena that are unique and complex. There is a certain regularity or pattern in it, but it is full of variations (diversity) in the facts contained in the problem being studied. Settlement of bad credit related to mortgage rights at Bank BRI Medan Thamrin Branch is preceded by steps taken by the bank to collect outstanding payments from debtors who have bad credit. The collection process is carried out through warning letters, telephone calls, or direct visits to debtors. If the debtor has not paid his obligations, the bank will then take steps to sell the assets through auction for the debtor's bad credit collateral. Regarding bills from taxpayers who are debtors of BRI Bank Medan Thamrin Branch, then if a taxpayer has an unpaid tax bill and he is a bank debtor, then the bank can withdraw funds from the taxpayer's bank account to pay the tax bill. This can be done based on a Tax Assessment Letter (SKP) issued by the tax authority which stipulates that the taxpayer must pay a certain tax bill. Settlement of debtors' bad debts at Bank BRI is related to taxpayers' tax debt claims against debtors. In an effort to provide legal certainty, the debtor's collateral object can be executed by the bank and then the sales proceeds are divided proportionally to the bank for bank credit debts and the tax office. on taxpayer debt.